2011
DOI: 10.2174/138920211794520150
|View full text |Cite
|
Sign up to set email alerts
|

LHON: Mitochondrial Mutations and More

Abstract: Leber’s hereditary optic neuropathy (LHON) is a mitochondrial disorder leading to severe visual impairment or even blindness by death of retinal ganglion cells (RGCs). The primary cause of the disease is usually a mutation of the mitochondrial genome (mtDNA) causing a single amino acid exchange in one of the mtDNA-encoded subunits of NADH:ubiquinone oxidoreductase, the first complex of the electron transport chain. It was thus obvious to accuse neuronal energy depletion as the most probable mediator of neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 82 publications
2
73
0
2
Order By: Relevance
“…More recently, the phenotypic spectrum has broadened to include neurodegenerative disease [ 72 ], typically as a function of a primary mtDNA defect. Leber's hereditary optic neuropathy (LHON) is the commonest cause of maternally inherited blindness and a cardinal example of how mtDNA mutations cause neurodegeneration [ 73 ]. MtDNA mutations (m.3460G>A, m.11778G>A and m.14484T>C in ~90 % of cases) in NADH-dehydrogenase subunits (complex I) reduce cellular energy and increase oxidative stress and ROS production to cause a selective loss of retinal ganglion cells (RGC) in the retina whilst sparing the retinal pigmented epithelium and photoreceptor layer [ 74 ].…”
Section: Primary Mitochondrial Disorders and Neurodegenerationmentioning
confidence: 99%
“…More recently, the phenotypic spectrum has broadened to include neurodegenerative disease [ 72 ], typically as a function of a primary mtDNA defect. Leber's hereditary optic neuropathy (LHON) is the commonest cause of maternally inherited blindness and a cardinal example of how mtDNA mutations cause neurodegeneration [ 73 ]. MtDNA mutations (m.3460G>A, m.11778G>A and m.14484T>C in ~90 % of cases) in NADH-dehydrogenase subunits (complex I) reduce cellular energy and increase oxidative stress and ROS production to cause a selective loss of retinal ganglion cells (RGC) in the retina whilst sparing the retinal pigmented epithelium and photoreceptor layer [ 74 ].…”
Section: Primary Mitochondrial Disorders and Neurodegenerationmentioning
confidence: 99%
“…Although approximately 45 mutations have been linked to LHON, all of the mutations identified in symptomatic individuals are secondary to amino-acid substitutions in the mitochondrial DNA coding for the respiratory chain subunits of the nicotinamide adenine dinucleotide ubiquinone oxidoreductase (complex I). Of the six mutations localized within this complex, the mutation in polypeptides ND1 (G3460A), ND4 (G11778A), and ND6 (T14484C) account for approximately 95% of all cases (Kirches 2011); mutation G11778 in ND4 appears to be the most common, accounting for 50-70% of all LHON. These latter mutations cause a defect in complex I function, resulting in the loss of energetic efficiency, increased oxidative stress, and an increase in the risk for apoptotic cell death.…”
Section: Nd4 Gene Therapymentioning
confidence: 99%
“…Whereas in the case of NDUFAF7, as a mitochondrial assembly factor, it is involved in mitochondrial respiratory chain system, 31 and previous research showed that the decline in ATP synthesis via mitochondrial energy metabolism leads to severe visual impairment. 32 Thus, we decided to focus on the function investigation of the mutant (MT) NDUFAF7 detected as a de novo missense mutation (p.D266E) in this family. As for RHO c.310G>A, it was found in RP patients, and no clear evidence of its pathogenicity has been reported.…”
mentioning
confidence: 99%